Peripheral Nerve Regeneration with Acellular Nerve Allografts Seeded with Amniotic Fluid-Derived Stem Cells - Xue Ma; Eileen Elsner; Jiaozhong Cai; Thomas L. Smith; Zhongyu Li (Stem Cells International)
Introduction. Tissue engineering strategies have attempted to mimic regenerating axons’ environment by adding supportive types of cells other than Schwann cell to the nerve allograft. We hypothesized that allografts can be seeded with amniotic fluid-derived stem cells (AFS) to promote nerve regeneration. Methods. ANAs with AFS cells for long-gap nerve repairs were studied using a rat model. A sciatic nerve injury was created and repaired immediately with a rat acellular nerve allograft (ANA) construct alone, an ANA construct seeded with AFS cells, or with an autograft. Walking track analysis and electrophysiology were performed to document the return of motor control at 4 months post injury. Axon morphology on the nerve segments was assessed. Results. In vivo gait analysis showed that the ANA plus AFS cell group had significantly advanced recoveries in overlap distance, paw angle degree, paw drag, stance width, axis distance, and sciatic function index (SFI) compared with ANA alone. The ANA plus AFS cell group also demonstrated greater gastrocnemius compound muscle action potential (CMAP) ratio, sciatic axon diameter, fiber diameter, myelin thickness, G ratio (average axonal diameter (AD)/fiber diameter (FD)), and neuromuscular junction (NMJ) numbers compared to ANA. Discussion. The allograft plus AFS cell group demonstrated significantly improved functional and histological outcomes compared to allograft group alone, showing no significant difference of the nerve regeneration from the autograft group. Thus, AFS cells may be a suitable cell source to replace Schwann cells to support and accelerate peripheral nerve regeneration following large-gap nerve injury.